Mutation and Lineage Analysis of DNMT3A in BCR-ABL1-negative Chronic Myeloproliferative Neoplasms - Huan-Chau Lin (International Journal of Gerontology, 2013)
In addition to the JAK2 V617F mutation, somatic mutation in DNMT3A has been described in BCL-ABL1-negative myeloproliferative neoplasms (MPNs). We have screened for DNMT3A exon 23 mutations in 130 adult Taiwanese patients with chronic phase myeloproliferative neoplasms. Only one somatic DNMT3A R882H mutation was identified in one JAK2 V617F mutation-positive essential thrombocythemia patient (1/91, 1%). Both mutations were detected in the CD34+-, CD19+-, peripheral blood mononuclear cell- and granulocyte-enriched fractions, but were not detected in the CD3+-enriched fraction by lineage analysis. Our findings suggest that DNMT3A mutation is not prevalent in MPNs, and further study is needed to clarify its role in the molecular pathogenesis of myeloproliferative neoplasms.